MAHKAMAH KONSTITUSI DAN KONTRAK OUTSOURCING - Ahmad Fadlil Sumadi (The Constitutional Court of the Republic of Indonesia, 2016)
The Amendment of the 1945 Constitution of the Republic of Indonesia has made the sovereignty still retained by the people, no more represented and fully held by the People’s Consultative Assembly like when the constitutional system of Indonesia was still embracing supremacy of parliament. In the constitutional perspective, the standing and relation between the state and people is becoming more obvious. Hence, in the case that constitutional dispute happened, there should have been an adjudication forum for solving the dispute. Therefore, Contitutional Court Of the Republic of Indonesia is established and designed constitutionally to solve the constitutional dispute through The Amendment of the 1945 Constitution of the Republic of Indonesia. Settlement of constitutional dispute through the review of constitutionality of norms in the regulation of outsourcing contract in The Labour Law at Contitutional Court of the Republic of Indonesia, with specific issue “the Contract of Employment for a specified time” that is regulated in Article 65 paragraph (7) and Article 66 paragraph (2) b of Labour Law is declaredconditionally unconstitutional.